2019
DOI: 10.1108/jd-12-2018-0214
|View full text |Cite
|
Sign up to set email alerts
|

Citations to chemical databases in scholarly articles: to cite or not to cite?

Abstract: Purpose Chemical databases have had a significant impact on the way scientists search for and use information. The purpose of this paper is to spark informed discussion and fuel debate on the issue of citations to chemical databases. Design/methodology/approach A citation analysis to four major chemical databases was undertaken to examine resource coverage and impact in the scientific literature. Two commercial databases (SciFinder and Reaxys) and two public databases (PubChem and ChemSpider) were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…At a minimum, the outputs of data-provisioning publications represent intellectual input by their authors and, in many cases, represent dozens or hundreds of hours of work and large financial investment (Agnarsson and Kuntner 2007; Ebach et al 2011; Baker and Mayernik 2020; Melville et al 2021). As has been broadly recognized in the literature, data producers deserve credit for their foundational work (Agnarsson and Kuntner 2007; Payne et al 2012; Penev et al 2017; Cousijn et al 2018, 2019; Kaufman et al 2018; Marwick and Birch 2018; Silvello 2018; Zhao et al 2018; Jones et al 2019; Lammey 2019; Pierce et al 2019; Tomaszewski 2019; Colavizza et al 2020; Dosso and Silvello 2020; Dorta-González et al 2021; Hood and Sutherland 2021). In a hypercompetitive academic environment where many aspects of an individual's career (e.g., reputation, career prospects, funding) are influenced by citation counts, this status quo for citation practice is neither fair nor sustainable (Agnarsson and Kuntner 2007; Neylon and Wu 2009; Payne et al 2012; Piwowar and Vision 2013; Tang et al 2017; Curry 2018; Gingras and Khelfaoui 2018; MacRoberts and MacRoberts 2018; Silvello 2018; Pierce et al 2019; Stern and O'Shea 2019; Colavizza et al 2020; Dosso and Silvello 2020; Raja and Dunne 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a minimum, the outputs of data-provisioning publications represent intellectual input by their authors and, in many cases, represent dozens or hundreds of hours of work and large financial investment (Agnarsson and Kuntner 2007; Ebach et al 2011; Baker and Mayernik 2020; Melville et al 2021). As has been broadly recognized in the literature, data producers deserve credit for their foundational work (Agnarsson and Kuntner 2007; Payne et al 2012; Penev et al 2017; Cousijn et al 2018, 2019; Kaufman et al 2018; Marwick and Birch 2018; Silvello 2018; Zhao et al 2018; Jones et al 2019; Lammey 2019; Pierce et al 2019; Tomaszewski 2019; Colavizza et al 2020; Dosso and Silvello 2020; Dorta-González et al 2021; Hood and Sutherland 2021). In a hypercompetitive academic environment where many aspects of an individual's career (e.g., reputation, career prospects, funding) are influenced by citation counts, this status quo for citation practice is neither fair nor sustainable (Agnarsson and Kuntner 2007; Neylon and Wu 2009; Payne et al 2012; Piwowar and Vision 2013; Tang et al 2017; Curry 2018; Gingras and Khelfaoui 2018; MacRoberts and MacRoberts 2018; Silvello 2018; Pierce et al 2019; Stern and O'Shea 2019; Colavizza et al 2020; Dosso and Silvello 2020; Raja and Dunne 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Recognizing the reliance of large data compilations on the many data-producing studies from which they are built, there is a growing consensus that data users should credit data producers in a way that is on par with the credit attributed to traditionally recognized outputs, like peer-reviewed publications (Piwowar and Vision 2013;Altman et al 2015;Penev et al 2017;Cousijn et al 2018;Kaufman et al 2018;Silvello 2018;Zhao et al 2018;Lammey 2019;Pierce et al 2019;Dosso and Silvello 2020). Despite this emerging consensus, the scientific community at large has been slow to adopt the practice of citing data sources, and a common procedure for data citation-used inclusively here to refer to any attribution to data provisioners by data users (e.g., Penev et al 2017;Cousijn et al 2018;Hood and Sutherland 2021; and see "Balancing Data Use and Citation in Paleontology")-remains elusive (Ingwersen and Chavan 2011;Marwick and Birch 2018;Zhao et al 2018;Cousijn et al 2019;Tomaszewski 2019;Silveira et al 2020;Suhr et al 2020). For example, in a review of 600 papers from 12 disciplines (e.g., biology, earth sciences, ecology, and environmental sciences; Zhao et al 2018), when authors used a new or existing dataset in their analysis (n = 312), data attribution was variable: 6% included data citations, 9% used unique identifiers for the data (e.g., DOI), 24% mentioned data with only a database name, and 60% referenced their data using a URL-an imperfect citation, given that URLs can expire.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the biggest advantages of depositing data in PubChem is that users can now search for UA thesis substance data with chemical specific search query options, such as by chemical structure, substructure, molecular formula, and identifier. Notably, there is limited information available about chemists' use of PubChem as citations to databases in the literature are rare (Tomaszewski 2019). In a recent information seeking behavior study of chemists, however, it was found that about 17 percent of the chemists surveyed use PubMed (Gordon et al 2018), which is closely integrated with PubChem.…”
Section: Pubchem Data Sharing Provenance and Accessmentioning
confidence: 99%
“…The “Cited Reference Search” tool has been successfully used to study citations to Wikipedia (Li et al, 2021 ; Park, 2011 ; Tomaszewski & MacDonald, 2016 ), chemistry handbooks (Tomaszewski, 2017 ), chemical encyclopedias (Tomaszewski, 2018 ), STEM databases (Tomaszewski, 2019 , 2021 ), MATLAB software (Tomaszewski, 2022 ), conference proceedings (Cardona & Marx, 2007 ), industry standards (Rowley & Wagner, 2019 ), news stories (Kousha & Thelwall, 2017 ), and tweets (Haunschild & Bornmann, 2023 ). This inspired the idea that a “Cited Reference Search” could be used to analyze citations to multiple bibliometric software tools.…”
Section: Introductionmentioning
confidence: 99%